Cosmopolitisme et politiques publiques : New York Ville Providence (1933‑1975) - Catherine Pouzoulet (L'Ordinaire des Amériques)
New York under the New Deal when, at city level, the La Guardia administration established the model of a welfare city, demonstrates that local public policies are a key component to a vibrant cosmopolitan tradition. This policy approach that attempted to give equal treatment to all neighborhoods did not survive the post-1975 financiarisation of the economy.